The Application of Animated Learning Videos to Learning Motivation - Siti Maslikah; Junaidi Budi Prihanto; Mochamad Budi Ridwan (Center for Sports Science , Faculty of Sport Science, Universitas Negeri Padang, 2026)
The purpose This study aims to determine the effect of the use of animated learning video media on increasing students' learning motivation in learning Physical Education, Sports and Health (PJOK) material on clean and healthy living behaviors in elementary schools. The background of this research focuses on the low motivation to learn PJOK in clean and healthy living behavior (PHBS) in elementary schools. This study uses a true experiment design in the form of a pretest–posttest control group design. The sample of this study is 26 students of class IV B designated as the control class and class IV D as many as 26 students as the experimental class. The research instrument is in the form of a learning motivation questionnaire with high validity and realism. Data analysis uses SPSS 25, namely descriptive analysis, normality test, paired sample t-test. The results obtained from the pretest and posttest showed a significant increase in learning motivation in the experimental group using animated learning video media compared to the control group